Fictional expectations and the global media in the Greek debt crisis: A topic modeling approach - Volker Daniel; Magnus Neubert; Agnes Orban (Humboldt University Berlin, 2018)
We study the role of global media during the Greek debt crisis and relate it to the transmission of events on financial actors' expectations. To identify news coverage about the Greek debt crisis, we apply topic modeling to a newly compiled dataset of over 430,000 articles from The International New York Times and Financial Times from 2009 to 2015. We identify a Greek debt crisis topic and relate it to events concerning Greece during this time period. Our finding is that events are only relevant for financial markets when they are covered in the media, whereas events without media coverage have no effect. News coverage without immediate events is equally irrelevant for financial markets.
urn:nbn:de:kobv:11-110-18452/19702-0
Keywords: D84; Z13; C55; G01; L82; 330; Greek Debt Crisis; Machine Learning; Topic Models; Expectations; Economic Sociology; Big Data; Financial Crises; Media